The Role of Indonesian Language Education in Facing the Society 5.0 Era: Curriculum Readiness to Face Technology and Innovation - Muh. Safar; Grace Citra Dewi; Loso Judijanto; Khalid Rahman (Journal of Pedagogi, 2025)
The Society 5.0 era requires education to adapt to technological developments in order to improve the quality of learning, including in Indonesian language education. Digital literacy is a crucial aspect in the curriculum so that students are able to think critically, filter information, and communicate effectively in the digital space. This study aims to analyze the readiness of the Indonesian language education curriculum in facing the challenges of Society 5.0 through a literature review study. Data sources were obtained from scientific journals, books, and education policy reports in the period 2014–2024. The results of the analysis show that the integration of technology in language learning has great potential in increasing student engagement and learning effectiveness through e-learning, artificial intelligence (AI), and interactive digital media. However, its implementation still faces challenges in the form of digital infrastructure gaps, lack of readiness of educators, and a curriculum that is not fully adaptive to technological developments. Therefore, a comprehensive strategy is needed, including improving digital infrastructure, training for educators, and collaboration between the government, educational institutions, and the technology industry sector. With these steps, Indonesian language education can become a main pillar in building a literate, critical, and innovative generation in the Society 5.0 era.